Pengaruh Model Penanaman Turnera Subulata terhadap Populasi H. armigera dan B. tabaci Serta Musuh Alaminya pada Tanaman Tomat (L. esculentum Mill.): The Effect of the Turnera Subulata Cultivation Model on H. armigera and B. tabaci Populations and Their Natural Enemies in Tomato (L. esculentum Mill.) - Ajeng Faradhila Muninggar; Nanang Tri Haryadi (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2023)
The tomato plant (L. esculentum mill) is a species of horticultural plant native to Latin America. It is one of the important horticultural plants and is included in the second largest vegetable after potatoes. Some of the main pests of tomato plants are B. tabaci and H. armigera which can lower production. Pest control using chemical pesticides can be reduced using growing refugia plants. This study was conducted to determine the effect of some models of reflux cultivation on natural enemy populations on tomato plants. This study used a Group Random Design consisting of 4 treatments: P0 (Control), P1 (Border Model), P2 (Strip Model), P3 (Random Model) each treatment was repeated 6 times. Research results show that the Border's reflux planting model has a good influence on the natural enemy population with the highest population obtained in the treatment of P1 (Border), with an average natural enemy population of 27 at most. This has a good effect on the decline of the pest population with the lowest average population obtained in the treatment of P1 (Border) and the highest pest population in the treatment of P0 (Control) at 2.85.